Anger Expression, Emotion Regulation and Mindfulness as Predictors of Conduct Problems in Children - Roeder, Mandy; Mueller, Anna R. (European Scientific Journal, ESJ, 2019)
Conduct problems and aggressive behaviors of children are serious problems for peers, parents and teachers of these children. To improve the understanding of conduct problems the present study investigates the links between difficulties in anger expression, emotion regulation, difficulties in impulse control and conduct problems. Moreover the relation of mindfulness and emotion regulation was of interest in the present study. To answer our research questions 310 elementary school children (157 boys, 153 girls) and their parents reported anger expression, emotion regulation strategies, mindfulness and conduct problems in a questionnaire. The results revealed that mindfulness was significantly related to anger expression and conduct problems. Moreover a regression analysis showed that anger expression mediated the relation of mindfulness and conduct problems. Child and parent reports were only weakly related if anger expression strategies that are hardly observable (Anger In, Anger Control) were considered. Relations were somewhat stronger for Anger Out. The findings are discussed and the relevance of mindfulness based emotion regulation is highlighted. The findings support the assumption that mindfulness, anger expression and emotion regulation are important aspects that influence child behavior.